Precipitation preferences alter the relative importance of herbaceous plant diversity for multifunctionality in the drylands of China - Guo, Hao; Zhou, Xiaobing; Tao, Ye; Yin, Jinfei; Zhang, Lan; Guo, Xing; Liu, Chaohong; Lin, Yajun; Zhang, Yuanming (Frontiers in Ecology and Evolution, 2023)
Multiple components of biodiversity are excellent predictors of precipitation-induced changes in ecosystem function. However, the importance of differing scales (alpha versus beta) is usually overlooked in biodiversity–ecosystem multifunctionality studies. Consequently, little is known about how precipitation regulates the relationship between multifunctionality and multiple components of alpha and beta diversity. We investigated geographic patterns of herbaceous plant diversity and ecosystem multifunctionality along a precipitation gradient spanning more than 2010 km in Northwest China. We assessed the effects of herbaceous species, phylogenetic, and functional components at different scales on multifunctionality in drylands. The alpha diversity of species and functional beta diversity were key components explaining the variation in multifunctionality. As the main environmental factor, MAP (mean annual precipitation) affected multifunctionality by changing the mediating variables (i.e., species alpha and functional beta diversity). More importantly, a certain precipitation threshold was detected for the relationship of multifunctionality to species alpha and functional beta diversity. MAPs of approximately 158 mm and 140 mm modulated this relationship (shifting it from uncorrelated to significantly correlated). Our findings provide insights into previously neglected mechanisms by which diversity in herbaceous layers at different scales affects ecosystem multifunctionality. It is highlighted that MAP regulates the relationship between diversity and multifunctionality in dryland ecosystems at different scales. Further, diversity may have substantial consequences for multifunctionality where MAP is higher. These empirical results provide a comprehensive understanding of the biodiversity–multifunctionality relationship in the context of precipitation, ultimately contributing to conservation and restoration programmes for multifunctionality in drylands.